2007
DOI: 10.1111/j.1747-5457.2007.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Isotope Stratigraphy of the Asmari Formation (Oligocene ‐ Lower Miocene), Sw Iran

Abstract: The Asmari Formation has been studied in the subsurface at the Bibi Hakimeh, Marun and Ahwaz oilfields and in an outcrop section from the Khaviz anticline. It consists of approximately 400 m of cyclic platform limestones and dolostones with subordinate intervals of sandstone and shale. The method of Sr-isotope stratigraphy is well suited for dating these strata because of the rapid rate of change of marine 87 Sr/ 86 Sr during Asmari deposition (roughly 32-18 Ma) and the common presence of well-preserved macrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 29 publications
(27 reference statements)
12
126
0
Order By: Relevance
“…Its lower boundary is characterized by a type 2 sequence boundary (Figure 8). The boundary (Sb III) is comparable with sequence surface Ch30 and with surface III reported by Ehrenberg et al [3] and by Van Buchem et al [4], respectively ( Figure 10). A parasequence consists of Mf2 (open marine; FA1), and Mf5 (semi restricted marine; FA2) form TST of Figure 10.…”
Section: Depositional Sequencesupporting
confidence: 74%
See 2 more Smart Citations
“…Its lower boundary is characterized by a type 2 sequence boundary (Figure 8). The boundary (Sb III) is comparable with sequence surface Ch30 and with surface III reported by Ehrenberg et al [3] and by Van Buchem et al [4], respectively ( Figure 10). A parasequence consists of Mf2 (open marine; FA1), and Mf5 (semi restricted marine; FA2) form TST of Figure 10.…”
Section: Depositional Sequencesupporting
confidence: 74%
“…4.5 of Hag et al [27], Figure 10). The boundary between this sequence and previous sequence (Sb I) is comparable with sequence surface Ru30/Ch10 proposed by Ehrenberg et al [3] and surface II reported by Van Buchem et al [4] (Figure 10). The transgressive systems tract (TST) of DS1 is marked by deposition of Mf1, Mf2 and Mf4.…”
Section: Depositional Sequencesupporting
confidence: 72%
See 1 more Smart Citation
“…These two reports were used by many authors (e.g., Seyrafian, 2000;Vaziri-Moghaddam et al, 2006;Amirshahkarami et al, 2007a, b). Recently, Ehrenberg et al (2007), Laursen et al (2009) and Van Buchem et al (2010) conducted strontium isotope dating to improve the biostratigraphic ages for the Asmari Formation across most parts of the Zagros basin (Izeh zone and Dezful Embayment) ( Table 2). This biozonation is used by many recent authors (e.g., Allahkarampour Dill et al, 2010;Van Buchem et al, 2010;Sooltanian et al, 2011;Rahmani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biostratigraphic characteristics of Asmari are revised and three assemblage zones and two subzones are introduced by [4]. [5] revised the biostratigraphy of the Asmari Foemation using strontium isotope. [6] also proposed new biozones for Asmari.…”
Section: Introductionmentioning
confidence: 99%